Upaya Peningkatan Ketahanan Ekonomi melalui Pendampingan Digital Marketing dan Design Kemasan Produk Olahan Kelor pada Pokdarwis Bahari Kota Mojokerto - Mohamad Johan Efendi; Rachmad Sholeh; Poppy Meilina D.H; Yeni Puspita; Reggy Risky Darmawan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
This community service program aims to strengthen local economic resilience through digital marketing assistance and packaging design innovation at Pokdarwis Bahari, Pulorejo Village, Mojokerto City. The intervention was designed in stages, including socialization, needs identification (FGD), training, practice/implementation, continuous mentoring, and evaluation. The program focused on strengthening production management (application of modern dryers and vacuum sealers), building digital marketing skills (creating and managing TikTok, Instagram, Facebook accounts, and online shops on Shopee and Tokopedia under the Pokdarwis Bahari brand), and redesigning packaging for kelor-based products (noodles, cakes, kelor sticks) to enhance product differentiation. The results showed significant improvements in members’ capacities: drying time reduced drastically from 2 days to 2 hours, the establishment of active digital accounts and official online stores, and the development of new packaging that is more informative and brand-identified. The direct impact was reflected in increased production efficiency, improved product image, and wider market reach—demonstrating a tangible contribution to local economic resilience and the sustainability of Pokdarwis businesses. Program recommendations include scaling up production technology, advanced training in digital marketing, and strengthening distribution networks to ensure long-term benefits.